Red creative : culture and modernity in China - O'Connor, Justin; Gu, Xin (Lecturer in communications and media studies) (Intellect, 2020)
Explores China's cultural economy over the last twenty years, particularly through the lens of its creative hub of Shanghai. Takes a long-term historical perspective and raises questions about the nature of contemporary creative capitalism and the universal claims of Western modernity, offering new ways of thinking about cultural policy in China.